Gene mutation profiling in microsatellite instability colorectal cancer and its association with the efficacy of immunotherapy: A retrospective study - Ying Liu; Kang Cui; Wang Ma (Cancer Medicine, 2024)
Abstract Background Microsatellite instability‐high (MSI‐H) colorectal cancer (CRC) is known for its heightened responsiveness to immunotherapy. However, establishing robust predictive markers for immunotherapy efficacy remains imperative. This retrospective study aimed to elucidate the genetic landscape of MSI‐H CRC and correlate these genetic alterations with immunotherapy outcomes in a cohort of 121 patients. Methods We analyzed clinical and molecular data from 121 patients with MSI‐H CRC. We conducted a thorough genetic analysis of MSI‐H CRC patients, with a specific emphasis on the APC, TP53, RAS, and MMR genes. We further analyzed the relationship between gene mutations and immunotherapy efficacy. The primary endpoints analyzed were objective response rate (ORR) and progression‐free survival (PFS). All statistical analysis was conducted using SPSS26.0 and R 4.2.0 software. Results Our findings underscored the complexity of the genetic landscape in MSI‐H CRC, shedding light on the intricate interplay of these genes in CRC development. Notably, mutations in MMR genes exhibited a distinctive pattern, providing insights into the underlying mechanisms of MSI‐H. Furthermore, our results revealed correlations between specific genetic alterations and immunotherapy outcomes, with a particular focus on treatment response rates and progression‐free survival. Conclusion This study represents a significant step toward unraveling the genetic nuances of MSI‐H CRC. The distinctive pattern of MMR gene mutations not only adds depth to our understanding of MSI‐H CRC but also hints at potential avenues for targeted therapies. This research sets the stage for future investigations aimed at refining therapeutic strategies and improving outcomes for patients with MSI‐H CRC.